GABAA receptor partially mediated propofol-induced hyperalgesia at superspinal level and analgesia at spinal cord level in rats - WANG QIN-yun; CAO Jun-li; ZENG Yin-ming; DAI Ti-jun (Acta Pharmacologica Sinica, 2016)
AIM: To observe effects of propofol on nociceptive response at superspinal and spinal level in rats. METHODS: Two hundreds and fifty-eight Sprague-Dawley male rats were randomized into thirty-two groups. Propofol and bicuculline were microinjected into lateral ventricle (icv), ventrolateral periaqueductal gray (vlPAG), intrathecal (ith), and intraperitoneal (ip). The noxious responses were evaluated by hot plate and formalin test. RESULTS: In hot-plate test, systemic and superspinal administration of propofol (40 mg.kg(-1) ip, 100 microg in 10 microL, icv, and 4 microg in 0.4 microL vlPAG microinjection) produced hyperalgesia (P